FUNGSI DPRD KOTA BATU DALAM DEMOKRASI: MENGAWAL ASPIRASI RAKYAT MELALUI KEBIJAKAN - Fariha Wahyu Utami; Vasya Nevia Aris Sandy; Putri Adelia Rahmawanti; Zakiya Rahma Fariyanto; Muhammad Fairuz Akmal; Muhammad Hisham Setiawan; Sri Untari (Universitas Negeri Malang, 2025)
The local government system in Indonesia, the existence of the Regional People's Representative Council (DPRD) has a very strategic position in bridging the needs of the community with local government policies. The purpose of this article is to find out the function of the DPRD in Democracy in safeguarding the aspirations of the people through policy. As a legislative body at the local level, the DPRD holds three main tasks, namely the formation of local regulations (perda), the function of supervising the running of local government, and the function of budgeting with the executive. This context becomes increasingly important in the midst of the complexity of regional socio-politics, where the relationship between DPRD, local government, and the community is dynamic. The method used is qualitative, namely conducting an interview. Based on the results of interviews with members of the Batu City DPRD, it is known that in practice the DPRD is active in preparing the RPJMD (Regional Medium-Term Development Plan), formulating the APBD (Regional Revenue and Expenditure Budget), and accommodating community aspirations through a recess mechanism that is carried out three times a year. DPRD also has a budget allocation through the right of main ideas to realize the needs of the community, proving its role as a representation of the people in the preparation of development programs. Community participation in the political process still faces challenges, especially from segments of society that are not yet politically empowered. Therefore, strategic steps are needed such as strengthening community-based recess mechanisms, utilizing digital technology, and empowering vulnerable groups through political education. Sistem pemerintahan daerah di Indonesia, keberadaan Dewan Perwakilan Rakyat Daerah (DPRD) memiliki posisi yang sangat strategis dalam menjembatani kebutuhan masyarakat dengan kebijakan pemerintah daerah. Tujuan artikel ini untuk mengetahui fungsi DPRD dalam Demokrasi menjaga aspirasi rakyat melalui kebijakan. Sebagai lembaga legislatif di tingkat daerah, DPRD memegang tiga tugas utama yakni pembentukan peraturan daerah (perda), fungsi pengawasan terhadap jalannya pemerintahan daerah, dan fungsi penganggaran (budgeting) bersama eksekutif. Konteks ini menjadi semakin penting di tengah kompleksitas sosial politik daerah, di mana hubungan antara DPRD, pemerintah daerah, dan masyarakat berlangsung dinamis. Metode yang digunakan adalah kualitatif yaitu melakukan sebuah wawancara. Berdasarkan hasil wawancara dengan anggota DPRD Kota Batu, diketahui bahwa dalam praktiknya DPRD aktif dalam menyusun RPJMD (Rencana Pembangunan Jangka Menengah Daerah), merumuskan APBD (Anggaran Pendapatan dan Belanja Daerah), serta menampung aspirasi masyarakat melalui mekanisme reses yang dilakukan tiga kali dalam setahun. DPRD juga memiliki alokasi anggaran melalui hak pokok-pokok pikiran untuk merealisasikan kebutuhan masyarakat, membuktikan perannya sebagai representasi rakyat dalam penyusunan program pembangunan. Partisipasi masyarakat dalam proses politik masih menghadapi tantangan, terutama dari segmen masyarakat yang belum berdaya secara politik. Oleh karena itu, diperlukan langkah-langkah strategis seperti penguatan mekanisme reses berbasis komunitas, pemanfaatan teknologi digital, dan pemberdayaan kelompok rentan melalui edukasi politik.